Pelaksanaan Zakat Hasil Pertanian di Kalangan Petani dan Pedagang (Toke) Salak Muslim di Kecamatan Angkola Barat Tapanuli Selatan - Silvia Harahap Harahap; Rosnani Siregar; Nurhalimah Lubis (Jurnal Ekonomi dan Bisnis Digital, 2026)
The agricultural sector in Indonesia has great potential, and Zakat serves as a solution to overcome poverty and empower the people. Given that most of the population in Angkola Barat District, South Tapanuli, depends on the salak (snake fruit) agricultural sector, the potential for Zakat from this sector is very large. However, awareness to pay Zakat on agricultural produce among salak farmers and traders in the area is still low. This research aims to determine the practice of implementing Zakat on salak agricultural produce and to analyze the factors causing the low awareness of salak farmers and traders (Toke) in paying Zakat. This research uses a qualitative research type with a case study method. The research subjects consisted of 16 salak farmers and traders from four villages in Angkola Barat District. Based on the research results, it is concluded that the awareness of salak farmers and traders (Toke) in fulfilling Zakat on agricultural produce is still very low, even though their nominal income has reached or even exceeded the nisab (minimum threshold for Zakat liability). The main factors influencing this low awareness include: Lack of understanding that agricultural Zakat must be paid immediately after the nisab is reached, without having to wait for the haul (one year of ownership), especially for agricultural products that are harvested multiple times a year, such as salak; the low level of education and the perception that Zakat only reduces income; the minimal educational role of Zakat institutions and religious leaders in socializing the obligation of agricultural Zakat, resulting in most only being familiar with Zakat Fitrah (Zakat paid during Ramadan); and the minimum presence of official institutions managing agricultural Zakat in the region.